Ex parte Milligan reconsidered : race and civil liberties from the Lincoln administration to the war on terror - Ex Parte Milligan at 150: the Constitution & Military Commissions in American wars on terror (Conference) (2016 : Illinois State University); Winger, Stewart Lance; White, Jonathan W., 1979- (Lawrence, Kansas : University Press of Kansas, 2020)
"In 1869, Justice David Davis of the US Supreme Court decided Ex parte Milligan, which held that citizens could not be tried under military commissions while civilian courts were still open and there was no war. Beginning already with Ex parte McCardle (1869), however, the Court seemed to hem in the Milligan precedent and disregarded it in subsequent cases. By 1991, the case was declared "irrelevant." All of that changed with the War on Terror and the invasions of Afghanistan and Iraq. In defense of their use of military tribunals, the Bush administration cited cases like Ex parte Quirin (1942) that upheld the use of a military tribunal for Nazi saboteurs. Rejecting such arguments, the Supreme Court has cited Milligan in four decisions, revitalizing interest in a case that had long seemed all but overruled. In doing so, the Court also effectively characterized Reconstruction as a "war on terror"-a war on the terrorist insurgencies against the assertion of black freedom by the Republican Party, the Union Army, and African Americans themselves. Ex parte Milligan Reconsidered explores the precedential power of Milligan and the questions it poses about the Civil War, the War on Terror, and executive power"--
Benjamin F. Butler, Ex parte Milligan, and the unending civil war -- Martial Law and the Expansion of Civil Liberties during the Civil War -- The Janus-Faced Character of Martial Law in the American Civil War, or the Strange Case of Lieutenant Alanson L. Sanborn and Dr. David M. Wright -- Race, Class, and Copperheadism : The Localist Foundations of Dissent in the Civil War's Middle Border -- "The State Was Honeycombed with Secret Societies" : Governor Oliver P. Morton and the Copperheads in Indiana -- "These Scoundrels Stand in No Fear of the Civil Courts; They Do, of the Military" : The Decision to Use Military Commissions to Try the Indiana Conspirators in 1864 -- Ex parte Milligan in Context and History : David Davis and the Constitutional Politics and Law of Civil Liberty -- To Leave Behind the Force of Law : Salmon Chase and the Civil War Era -- The Least Naive Position : The Lincoln Administration and International Law in American Wars on Terror -- Ex parte Milligan in the State Courts : Madison Y. Johnson's Vindication in Illinois -- Ex parte Milligan in Context and History : From Reconstruction to the War on Terror -- Ex parte Milligan and the War on Terrorism : Testing the Constitutional Bedrock of a Civilian Criminal Trial.
Includes index.
Description based on print version record.
Keywords: War and emergency powers -- United States -- Congresses; Civil rights -- United States -- History -- Congresses; Executive power -- United States -- History -- Congresses; Civil supremacy over the military -- United States -- History -- Congresses; Courts-martial and courts of inquiry -- United States -- History -- Congresses; War on Terrorism, 2001-2009 -- Congresses; Milligan, Lambdin P. -- Trials, litigation, etc; Ex parte Milligan, 71 U.S. 2 (1866)